(untitled) (Revista Brasileira de Plantas Medicinais, 2020)
Pest and disease control are critical processes for the agricultural industry and typically require the application of large amounts of at least one chemical compound on the plant or soil for treatment. However, herbal extracts can be used to provide crop protection against attack by pathogens, reducing the detrimental and toxic effects on humans and the environment. Therefore, the aim of this study was to assess the in vitro effect of twelve plant extracts PN01 (Alternanthera dentata), PN02 (Alternanthera tenella), PN03 (Ipomoea alba), PN04 (Allamanda blanchetii), PN08 (Lippia alba), PN09 (Plantago major), PN12 (Solanum cordifolium), PN11 (Cecropia glaziovii) PN13 (Solanum torvum), PN17 (Rhizophora mangle), PN18 (Chamomilla recutita) and PN20 (Melissa officinalis) on growth of Colletotrichum musae, post-harvest rot of banana and evaluate the potential cytotoxicity by using Artemia salina model. The extract PN03 showed the greatest potential for control, reducing by 78% in the growth of Colletotrichum musae; PN01, PN04, PN08, PN10, PN12 and PN13 inhibited the fungal growth by 45.5%, 22.9%, 59.1%, 43.8%, 44.3% and 60.0%, respectively. On the other hand, PN11, PN02, PN09 and PN17 did not present activity. Only extracts PN01, PN02, PN10, PN11 and PN12 showed toxicity to brine shrimp. By the analysis of the chromatographic profile, these extracts showed a predominance of polyphenols. Considering these species are found abundantly in the flora, these results may indicate an alternative and accessible control of postharvest rot.